2023
DOI: 10.3390/plants12040748
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Development of Genome-Wide Microsatellite Markers for Stock (Matthiola incana L.)

Abstract: Stock (Matthiola incana (L.) R. Br.) is a famous annual ornamental plant with important ornamental and economic value. The lack of DNA molecular markers has limited genetic analysis, genome evolution, and marker-assisted selective breeding studies of M. incana. Therefore, more DNA markers are needed to support the further elucidation of the biology and genetics of M. incana. In this study, a high-quality genome of M. incana was initially assembled and a set of effective SSR primers was developed at the whole-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…In this study, a total of 54526 SSRs were discovered from the cashew genome, with a mean density of 153 SSRs/Mb. The density of markers found in this study was higher than that reported in apple (40.8 SSRs/Mb, 485 Mb) ( Zhang et al., 2021b ), Chinese spring wheat (36.68 SSRs/Mb, 9.93 Gb) ( Han et al., 2015 ), and Matthiola incana (23.25 SSRs/Mb, 1977.48 Mb) ( Tan et al., 2023 ), while it was less than mango (418.17 SSRs/Mb, 253.6 Mb) ( Ravishankar et al., 2015 ), Prunus mume (794 SSRs/Mb, 237 Mb) ( Sun et al., 2013 ), and Pomegranate (527.97 SSRs/Mb, 296 Mb) ( Patil et al., 2020 ), suggesting that generally, the density of SSRs decrease with an increase in the genome size. Further, the frequency of perfect SSRs (87.39%) was much higher than the frequency of imperfect SSRs (12.61%) in the discovered genome-wide SSRs and is consistent with similar results in eggplant ( Portis et al., 2018 ), Anemone coronaria ( Martina et al., 2022 ), and Aristotelia chilensis ( Bastías et al., 2016 ).…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, a total of 54526 SSRs were discovered from the cashew genome, with a mean density of 153 SSRs/Mb. The density of markers found in this study was higher than that reported in apple (40.8 SSRs/Mb, 485 Mb) ( Zhang et al., 2021b ), Chinese spring wheat (36.68 SSRs/Mb, 9.93 Gb) ( Han et al., 2015 ), and Matthiola incana (23.25 SSRs/Mb, 1977.48 Mb) ( Tan et al., 2023 ), while it was less than mango (418.17 SSRs/Mb, 253.6 Mb) ( Ravishankar et al., 2015 ), Prunus mume (794 SSRs/Mb, 237 Mb) ( Sun et al., 2013 ), and Pomegranate (527.97 SSRs/Mb, 296 Mb) ( Patil et al., 2020 ), suggesting that generally, the density of SSRs decrease with an increase in the genome size. Further, the frequency of perfect SSRs (87.39%) was much higher than the frequency of imperfect SSRs (12.61%) in the discovered genome-wide SSRs and is consistent with similar results in eggplant ( Portis et al., 2018 ), Anemone coronaria ( Martina et al., 2022 ), and Aristotelia chilensis ( Bastías et al., 2016 ).…”
Section: Discussioncontrasting
confidence: 76%
“…AT/TA repeat motifs (62.44%) were most frequently distributed in di-nucleotides. It has also been observed in Matthiola incana [43], rice [44], Fagopyrum tataricum [45], and other species. This may be the reason for the higher number of slips in shorter repetitions [46].…”
Section: Development Of Novel Microsatellite Markers For Population S...mentioning
confidence: 78%
“…Genetic markers, which encompass any observable or testable phenotype, as well as the genetic basis for assessing the observed phenotypic variability, are collectively known as. There are three categories for genetic markers: morphological and productive features, which are visually determined; biochemical markers, which are based on gene products; and molecular markers, which are based on DNA analysis (Sudan et al, 2016;Tan et al, 2023). The study samples revealed two genetic polymorphisms, 270/260 and 280/271, with significantly different percentages of 63.79 (2010) pointed out the high productivity potential of using techniques for estimating and preserving genetic material, as well as emphasizing that genetic markers have a role in preserving animal breeds.…”
Section: Coefficient Of Heat Tolerance Milk Flow Rate and Mastitismentioning
confidence: 99%